Strengthening Person Organization Fit and Innovative Work Behavior Through Psychological Capital and Leader-Member Exchange - Purnama, Ika Rezki; AC, Ahmad; Rendra Anggoro, Yusuf Alfian (Golden Ratio of Human Resource Management, 2024)
This study investigates the interrelationships among Psychological Capital, Leader-Member Exchange (LMX), Person-Organization Fit (POF), and Innovative Work Behavior (IWB) within the context of the construction industry in Makassar. The research aims to determine the direct and indirect effects of Psychological Capital and LMX on POF and, subsequently, on IWB among employees. Specifically, the study poses the following research questions: (1) Does Psychological Capital influence Person-Organization Fit among construction company employees? (2) What is the impact of Leader-Member Exchange on Person-Organization Fit in this setting? (3) How do Psychological Capital and Leader-Member Exchange directly affect Innovative Work Behavior? (4) Do Psychological Capital and Leader-Member Exchange indirectly influence Innovative Work Behavior through Person-Organization Fit? The significance of this research lies in its potential to enhance understanding of key human resource constructs and their interplay, which could inform the development of HR management practices. Moreover, the findings are expected to provide actionable insights for construction companies aiming to foster a culture of innovation among their workforce. The methodology encompasses the collection of primary data from 397 employees across various construction companies, employing proportional stratified random sampling to select 199 respondents based on the Slovin Formula with a 5% precision level. Path analysis is conducted using the AMOS 24 software to analyze the data. The anticipated outcomes of this research include the establishment of significant relationships between Psychological Capital and both Person-Organization Fit and Innovative Work Behavior, as well as between Leader-Member Exchange and Person-Organization Fit. Furthermore, the study seeks to explore whether Psychological Capital and Leader-Member Exchange can enhance Innovative Work Behavior mediated by Person-Organization Fit. The results aim to contribute both theoretically to academic discourse and practically as a resource for organizational development in the construction sector.